Legal protection of the electronic shop - Nouasria, Zahra (Journal of Human Sciences, 2022)
The electronic shop, as e-commerce, is a fact that must not be ignored, As a traditional trade, a commercial site can qualify as a business if it gathers a certain number of elements. In order to assert the existence of an electronic commerce fund, it is appropriate to attribute to it the elements constituting a classical business fund, the qualification entails several legal consequences, in particular the protective regime applicable to it. The Algerian legislator did not regulate the electronic store with special legal rules, We have tried to apply in this article the legal regime of classical commerce on the basis of electronic commerce in order to achieve the legal protection of the latter.